1-(4-Alkyloxybenzyl)-3-methyl-1H-imidazol-3-ium organic backbone: A versatile smectogenic moiety - William Dobbs (Beilstein Journal of Organic Chemistry, 2009)
The merger of ionic liquid and liquid crystal fields, obtained by using the imidazolium ring as a common element, has allowed us to tailor a new set of materials which associate specific functionalities. These functionalities are consequences of the original properties of the component, ionic liquids, liquid crystals and their association in a single compound. The study of this interesting association led us to elaborate environment-flexible cationic architectures from which mesomorphic properties emerge. Moreover, we have also explored the influence of different anions on the mesomorphic properties.